Workability, strength and toughness properties of different types of fiber-reinforced wet-mix shotcrete. (June 2021) - Guler, Soner; Öker, Behice; Akbulut, Zehra Funda
Abstract: The main focus of this study is to investigate the effects of macro steel (ST), forta-ferro (FF) and polyamide (PA) synthetic fibers on the slump, compressive, splitting tensile, flexural strength, flexural toughness and rebound rate of wet-mix shotcrete. The toughness capacities of fiber reinforced shotcrete (FRS) mixes was also evaluated in accordance with the JSCE SF-4 and CECS 13-2009 standards. The fiber volume fractions added into the shotcrete mixes are 0.25%, 0.5%, and 1%. The test results showed that when the fiber ratio is increased from 0.25% to 1%, slump values for all the FRS mixes decreased significantly and the highest decrease occurred for the PAFRS mixes. The ST fibers are highly more effective than PA and FF synthetic fibers to enhance the strength and toughness capacities of concrete due to ST fibers have higher tensile strength and outstanding geometrical shape. The CECS 13-2009 and JSCE-SF4 standards are sufficient to calculate the toughness capacities of FRS specimens up to their limit deflection values. However, if higher deflection values were used by these two standards, the significant contribution of all fibers in the inelastic region would be more realistically taken into account.